Economic Losses Due to Forest Fire as a Climate Change Incidences in Sidhababa Community Forest of Bara District, Nepal - Manjan, Shiv Kumar; Ansari, Yusuf (Indian Forester, 2016)
Climate change is major concern of the world due to global warming. It plays vital role to increase forest fire incidences and causes huge economic losses and human death. Fire-induces loss of soil cover negatively affects hydrological regimes and soil properties. Therefore the research was conducted on this topic. The field work approaches included forest inventory and contingent valuation. Similarly laboratory test, secondary data and formulae assumed to conclude the result of carbon emission and loss in sequestration and their economic values. The economic loss due to burning of timber, leaf litter, fuel wood of the forest and emission of CO2 due the burning of leaf litter, timber and fuel wood was estimated as IRs. 96686.04per hector per annum in the community forest. Sequestration losses were not found in the forest because there was no damage caused in standing trees during the surface forest fire. The most devastating crown forest fire was not recorded in the forest. But small shoots of the regeneration and NTFPs was found to be damaged. On return of favorable condition most of the regenerations and NTFPs again come up but very small and intolerable seedlings was seen as completely damaged due to forest fire.